Understanding Russianness - Alapuro, Risto, 1944-; Mustajoki, Arto S. (Arto Samuel), 1948-; Pesonen, Pekka (London ; New York : Routledge, 2012)
In today's world where other cultures are being tapped to a greater extent than ever before, the processes of mixing and matching are especially relevant in making sense of Russia. Not only do borrowing and assimilation, interaction between the familiar and the alien, constitute a venerable tradition in Russian culture, but during the two last post-Soviet decades a notable Western influence has become apparent. This book provides means for understanding Russianness in this new situation. By bringing together Russian and Western, eminent and younger scholars it provides insights both from inside and outside. By extending its perspectives to three fields - linguistics, cultural studies, and social sciences - it covers different dimensions of creative misunderstandings , hybrids, tensions and other modes of adaptation in the Russian culture. By offering concrete case studies it avoids easy stereotypes, deconstructs clichés, problematizes accepted truths, and identifies points of interaction between Russia and the West. -- Book Description.
Language -- The "west" in the linguistic construction of Russianness in contemporary public discourse -- Attitudes toward the Russian and English languages in Russia and the United States : perceptions of self and the other -- Russification of western concepts : political will and crisis in a Russian way -- A Russian view of western concepts -- Society -- Russian "otherness" : from Chaadaev to the present day -- From a mother's worry to soldiers' mothers action : building collective action on personal concerns -- Opposition substitutes : reflections on the collective action in support of the European University at St. Petersburg -- Political culture in Russia in a local perspective -- Soviet modernity : the case of Soviet fashion -- Culture -- Spiritus loci : two east Karelian folklore epic traditions -- Autogenesis in Russian culture : an approach to the avant-garde -- Two hundred years of poshlost : a historical sketch of the concept -- The notion of universal bisexuality in Russian religious philosophy -- Religious nationalism in contemporary Russia : the case of the Ossetian ethnic religious project -- Social networking on the internet : is the Russian way special?.
Includes bibliographical references and index.
Also issued online.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social psychology -- Russia (Federation); Group identity -- Russia (Federation); Ethnicity -- Russia (Federation); Russia (Federation) -- Social life and customs; Electronic books